PENGARUH CITRA MEREK DAN DAYA TARIK PROMOSI TERHADAP MINAT BELI KONSUMEN PADA ORIFLAME MALL SKA PEKANBARU - Tsaadah, Asnurhaya; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Currently, many beauty products in Pekanbaru are experiencing quite significant development in Pekanbaru, one of which is Oriflame. This research aims to determine how much influence brand image and promotional attractiveness have on consumer buying interest at Oriflame mall SKA Pekanbaru, both partially and simultaneously. This type of research is quantitative research. The population in this study were visitors to the SKA Pekanbaru Mall, totaling 3,912 people. By using the Solvin formula and getting 97 samples. To prove the proposed hypothesis, the analytical techniques of Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis and F Test, t Test are used. The results of this research show that based on data obtained by 97 respondents and processed by researchers, that there is an influence of brand image and promotional attractiveness on consumer buying interest at Oriflame Mall SKA Pekanbaru. This can be seen from the large R² of this research which is 77.4%. This shows that the percentage of influence of brand image and promotional attractiveness on consumer buying interest at Oriflame Mall SKA Pekanbaru is 77.4%. which is included in the High category level. If the coefficient interval is 80% - 100%, it is considered a very influential level, while the remaining 22.6% is influenced by other variables not included in this study. Keywords: Brand Image, Promotional Attraction, Purchase Interest, Oriflame Pekanbaru